Screening of antimicrobial activity and cytotoxic effects of two Cladonia species - ÇOBANOĞLU, GÜLŞAH; SESAL, NÜZHET CENK (Verlag der Zeitschrift fur Naturforschung, 2013)
The present study explores the antimicrobial activity and cytotoxic effects in culture assays of two fruticose soil lichens, Cladonia rangiformis Hoffm. and Cladonia convoluta (Lamkey) Cout., to contribute to possible pharmacological uses of lichens. In vitro antimicrobial activities of methanol and chloroform extracts against two Gram-negative bacteria (Pseudomonas aeruginosa and Escherichia coli), two Gram-positive bacteria (Enterococcus faecalis and Staphylococcus aureus), and the yeast Candida albicans were examined using the paper disc method and through determination of minimal inhibitory concentrations (MICs). The data showed the presence of antibiotic substances in the chloroform and the methanol extracts of the lichen species. The chloroform extracts exhibited more significant antimicrobial activity than the methanol extracts. However, a higher antifungal activity was noted in the methanol extract of C. rangiformis. The maximum antimicrobial activity was recorded for the chloroform extract of C. convoluta against E. coli. The cytotoxic effects of the lichen extracts on human breast cancer MCF-7 cells were evaluated by the trypan blue assay yielding IC50 values of ca. 173 and 167 μg/ml for the extracts from C. rangiformis and C. convoluta, respectively. © 2013 Verlag der Zeitschrift für Naturforschung, Tübingen.
Keywords: Antimicrobial Activity; Cladonia; Lichen; MCF-7